Starość – sędziwość – dojrzałość. „Senex” i „senectus” w literaturze galijskiej V-VI wieku - Żurek, Antoni (Vox Patrum, 2011)
The theme of old age is presented only occasionally by Latin authors who wrote their works in Gallia in the 5th and 6th centuries after Christ. The term „old man” is first and foremost a man of advanced age. Nowhere, however, a limit of old age is defined. Usually one can find a reference to a man still vital, though bearing the hallmarks of loss of strength and fitness. Old age is sometimes linked up with infirmity. Nowhere, however, one talks about any special care that these old people or the old with symptoms of old age need. In a positive sense old age means a person who has experience and authority. People of the Church who enjoy respect are often described in this way. Reaching old age understood in this sense was seen as an expression of God`s blessing.